KONSTRUKSI PENGALAMAN MAHASISWA PENDIDIKAN AGAMA ISLAM YANG BEKERJA PART-TIME DALAM MENGELOLA WAKTU PERKULIAHAN - Tengku Indah Syafira; Dinda Sa’adah; Muhammad Burhan Nasrulah; Zainal Abidin (Islamijah: Journal of Islamic Social Sciences, 2026)
This study aims to understand the experiences of sixth-semester Islamic Religious Education (PAI) students at UIN Sumatera Utara who work part-time in managing their study time through a phenomenological approach. The focus of the study includes the dynamics of daily routines, time management strategies, psychological stress, the impact on personal development, and the role of social and institutional support. The study used a qualitative method with a phenomenological approach. The research subjects consisted of 10 sixth-semester PAI students who actively work part-time. Data collection techniques were carried out through in-depth interviews, observation, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results show that students who work part-time experience time fragmentation due to busy academic and work activities. To overcome this, students develop various strategies such as preparing daily schedules, determining priorities, and utilizing free time effectively. In addition, students also experience psychological stress in the form of fatigue and stress, but are able to overcome these through coping mechanisms, especially religious approaches. This study also found that work experience has a positive impact on students' personal development, such as increased independence, responsibility, communication skills, and social skills. The support of family and friends is a crucial factor in helping students maintain a balance between study and work. This study shows that Islamic Religious Education students are able to develop adaptability and time management skills while juggling their dual roles as students and part-time workers.Keywords: time management, part-time student workers, phenomenology, Islamic Religious Education students, student experiences.